Revolutionizing Concrete Bridge Assessment: Implementing Nondestructive Scanning for Transformative Evaluation - Wael Zatar; Felipe Mota Ruiz; Hien Nghiem (Applied Sciences)
This study focused on analyzing the impact of ground-penetrating radar (GPR) scan spacing on accurately assessing the reinforcement of concrete bridge girders, providing practical insights. A decommissioned bridge box beam was evaluated to unveil rebars and tendons’ depth and spacing. The box beam was decommissioned from the West Virginia Division of Highways inventory. An innovative algorithm was developed to fully automate the analysis of survey grid data across all sides of the beam. Implementing this algorithm into a computer code has paved the way for comprehensive automation of GPR data analyses. Comparing GPR data analyses from various profile line offsets, this study assists in producing optimal protocols for inspecting box beams. Transverse profile line offsets between 4 in. and 24 in. yielded nearly identical results, setting a new standard for precision. Utilizing more than one longitudinal profile line was highly beneficial in accurately assessing prestressed concrete box beams. This research helps redefine bridge evaluation by precisely finding rebar spacing, concrete cover, and other internal characteristics. This study’s findings offer invaluable advancements and equip state departments of transportation with the knowledge to accurately assess in-service concrete bridge box beams, empowering them to make informed decisions.